Identifying Habitat Characteristics and Critical Areas for Irrawaddy Dolphin, Orcaella brevirostris: Implications for Conservation - Cindy, Peter; Anna Norliza, Zulkifli Poh; Jenny, Ngeian; Andrew Alek, Tuen; Gianna, Minton (Springer International Publishing, 2016)
Irrawaddy dolphins, Orcaella brevirostris, in the Kuching Bay, Sarawak, Malaysia have been subjected to pressure from cetacean-fisheries interactions, dolphin watching tourism and coastal development. However, very little information is known about their ecology and factors driving their habitat preferences. To obtain critical information on the distribution, habitat preference and range pattern of Irrawaddy dolphins in Kuching Bay, Sarawak, systematic boat-based surveys were conducted between June 2008 and October 2012. The results showed a statistically significant relationship between Irrawaddy dolphins’ distribution and different categories of salinity, tide levels and distance to river mouths. Kruskal-Wallis tests confirmed that the presence of Irrawaddy dolphins in Kuching Bay had statistically significant relationships to habitat parameters of salinity (chi-square = 4.694, p = 0.03). Fisher’s exact test indicated that Irrawaddy dolphins were statistically more likely to be present in waters within a 6 km radius of river mouths. The distribution of dolphins was also affected by tide levels as Mann-Whitney U-tests proved a statistically significant difference in dolphin distribution between tide levels lower than 2.0 m and tide levels higher than 2.0 m (p = 3.153 × 10−11). The representative range and core area of photo-identified Irrawaddy dolphins estimated using fixed kernel range was 246.42 km2 and 37.22 km2, respectively, with core area located in the Salak Estuary. The results obtained in this study reflect dry season distribution only, and may differ during the wet season. Nonetheless, these results highlight the importance of shallow coastal waters and the overlap of Irrawaddy dolphin critical habitat with that of human activities in Kuching Bay. Conservation efforts are required to minimise the effects of the pressures exerted on these animals and their habitats.